Donor-specific graft injury in solid organ transplantation: potential mechanisms and therapeutic strategies - Yang, Chengliang; Shannon, Casey P.; Zhao, Hedi; Tebbutt, Scott J. (Frontiers in Transplantation, 2024)
Organ transplantation is the most effective therapy for end-stage disease patients. In addition to organ donation after brain death (DBD), which is common in clinical practice, organ donation after circulatory death (DCD) is one of the solutions to the growing demand for transplanted organs. In this paper, we discuss insights gained from comparing DBD and DCD allografts. These comparisons suggest that different types of donors may lead to different patterns of graft dysfunction and recovery in recipients, requiring different evidence-based therapies due to donor-specific injury.